Damage Detection in Ceramic Materials Using Bicoherence Analysis - (:unkn) unknown (My University, 2020)
In this study, Bicoherence method was applied to analyze the state of 6 ceramic plates made from the same material is cracked or not. Of all six plates, while 1 consisted of an undamaged plate, the other 5 comprised of cracked plates. Cracks in damages plates have non-identical deformations. The centre points of the plates were applied to shock at equal severity by means of the pendulum. The sound, which emerged as a result of the impact, was recorded and transferred to the data processing environment. A single bicoherence peak was observed at the centre of the durable plate and more than one peak was seen in the cracked plates by the analysis conducted, in addition, their magnitudes were so much smaller than those of durable plates. While large rising magnitudes were formed at the centre on the bi-coherence plane of the durable ceramic plate, more than one bicoherence peaks, with low magnitudes, were formed on the cracked ceramic plates. Differentiation and feature extraction can clearly be identified in the feature diagonal slice analysis of the cracked plates with the bicoherence analysis carried out. While maximum bicoherence coordinates were formed in the coordinate centre of the durable ceramic plate, deviation from the centre presented itself in the cracked ceramic plates.